COMMENTS ON THE ARTICLE BY M.M. SADYKOV, L.S. GRISHINA, R.R. NIYAZOV, L.YE. ZIGANSHINA «CLINICAL PHARMACOLOGICAL SERVICE IN OPTIMIZATION OF THE PHARMACOLOGICAL SUPPORT AT THE INITIAL STAGE OF THE PEDIATRIC CARE» - A.S. Kolbin (Педиатрическая фармакология)
.